Fake Radiolab: Audio and Ideology - Akiva Zamcheck; Adam Mirza (Current Musicology, 2023)
Fake Radiolab is the name of an ongoing duo performance project in which we interrogate mediated “facts” through explorations in the podcast media form. We adopt the mannerisms and mania of radiophonic personalities and a variety of media genres (e.g., podcasts, YouTube rants, ASMR sessions, self-help narrations, dream sequences, radio plays, nature documentaries) to playfully/seriously jar the clarity and authority imparted to “content” by contemporary audio production. Acting as (unreliable) hosts of a live podcast, we present a kind of musicalized speech performance that juxtaposes multiple modes of audio narration against live synths, processed violin, and sampled audio fragments. During live performance, the opening narration, which is pre-recorded, presents an acousmatic pun to the audience who sees us on stage in front of our microphones; instead, our improvised performance inserts other manipulated material in counterpoint to the pre-recorded “backing-track.”